Penciptaan Kostum Tari Wayang Wong Ngereka Seraga Japatuan - Adnyana, I Ketut Agus Putra; Mertanadi, I Made; Berata, I Made (Hastagina : Jurnal Kriya Seni, 2024)
The existence of the Wayang Wong Mask in community interlocution events in the current era has experienced a downturn, which in fact is low in appreciation and a decline in the interest of the millennial generation in its continuation. This phenomenon is because wayang wong dances are mostly performed on certain days, and most wayang wong dances are sacred arts. This very interesting issue was raised as a basis for the creation of new creative wayang wong mask costumes, in the form of creating a wayang wong dance costume set which was packaged innovatively entitled "Wayang Wong Ngereka Seraga Japatuan Dance Costume", which is an interpretation of the visualization of Geguritan Japatuan in the form of a costume set. wayang wong dance. The creation of the Wong Ngereka Seraga Japatuan Wayang Dance Costume works uses a creation method which consists of three stages of creation, namely: exploration, design and realization. Exploration includes activities to explore sources of ideas by identifying and formulating problems regarding creative sources in interpreting Ngereka Seraga Japatuan. Design, ideas are built based on obtaining important points from the results of the analysis which are formulated in the visualization of ideas in alternative sketch forms as design references. Realization, making a model according to a sketch or technical drawing that has been prepared into a prototype model until it reaches the complete form of the work and can represent the substance of Gaguritan Japatuan.